KONSEP SADD AL-ZARAI’ DAN AKTUALISASINYA DALAM TRANSAKSI JUAL BELI - Ibrahim, Muhammad Iqbal; Putra, Trisno Wardy (Universitas Muhammadiyah Makassar, 2021)
Preventive action by closing or prohibiting something that is basically permissible to prevent mafsadah or damage that is feared to occur if this is allowed. Thus sometimes people translate the meaning of the concept of sadd al-żarāi '. Lots of books or papers that explain this rule and its application, ranging from food problems such as the prohibition of selling food products that are not equipped with a halal label from the MUI and a list of POM numbers which basically sell food and medicine is including muamalah that is allowed in Islam, however, because it is feared that it contains substances that are forbidden or contain chemicals that are harmful to the body, so it is prohibited.Keywords: Sadd Al-Zarai 'Concept, Actualization, Transaction